Meeting models and mineralogy. (March 2018) - Bridges, John
A new geochemical study shows that short-lived warm and wet episodes during a globally cold early Mars could have formed the clay deposits detected on the Martian surface. This model can reconcile climate models with mineralogical and geomorphological evidence.